Biological effects of combinations of structurally diverse human milk oligosaccharides - Wichmann, Anita (Frontiers in Pediatrics, 2024)
Human milk oligosaccharides (HMOs) are a diverse group of structures and an abundant bioactive component of breastmilk that contribute to infant health and development. Preclinical studies indicate roles for HMOs in shaping the infant gut microbiota, inhibiting pathogens, modulating the immune system, and influencing cognitive development. In the past decade, several industrially produced HMOs have become available to fortify infant formula. Clinical intervention trials with manufactured HMOs have begun to corroborate some of the physiological effects reported in preclinical studies, especially modulation of the gut microbiota in the direction of breastfed infants. As more HMOs become commercially available and as HMOs have some shared mechanisms of action, there is a need to better understand the unique and differential effects of individual HMOs and the benefits of combining multiple HMOs. This review focuses on the differential effects of different HMO structural classes and individual structures and presents a scientific rationale for why combining multiple structurally diverse HMOs is expected to exert greater biological effects.